한·중 간 농축산물 생산비 격차 변동요인 - 문한필 (한국농촌경제연구원, 2013)
The FTA negotiation between Korea and China was formally launched in May 2012. Agriculture in two countries has similar production structure and development path, but also has distinctive resource endowments and growth stages, which lead to the current price competitiveness of Chinese agricultural products in the Korean market. Recently, however, production costs in Chinese agriculture are continuously increasing so that the gaps of production costs and retail prices in most agricultural products between Korea and China are gradually narrowing. The sharp rises of input prices including agricultural wage and land rent in China are likely to threaten the price competitiveness of Chinese agricultural export. The appreciation of the Chinese currency is another driving factor bridging these gaps. In the long run, this pattern could contribute to competitiveness enhancements of Korean agricultural products over Chinese ones. Negotiation strategies taking this pattern into consideration are required to acquire more favorable concessions in the Korea-China FTA.